2020
DOI: 10.1101/2020.12.25.424183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating performance of existing computational models in predicting CD8+ T cell pathogenic epitopes and cancer neoantigens

Abstract: T cell recognition of a cognate peptide-MHC complex (pMHC) presented on the surface of infected or malignant cells are of utmost importance for mediating robust and long-term immune responses. Accurate predictions of cognate pMHC targets for T Cell Receptors (TCR) would greatly facilitate identification of vaccine targets for both pathogenic diseases as well as personalized cancer immunotherapies. Predicting immunogenic epitopes therefore has been at the centre of intensive research for the past decades but ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 58 publications
1
16
1
Order By: Relevance
“…Off-rates predicted by online utilities were inconsistent not only with measured values but with each other, both in order of magnitude and in rank order of peptides, though they correctly predicted which peptides would bind poorly. Previous authors have made similar observations; a recent study evaluating performance of computational models in predicting CD8+ epitopes found that no existing algorithm performs ‘substantially’ better than random [ 22 ], and a study introducing MHCflurry, an MHC-I binding affinity prediction package that the authors present as an improvement over NetMHC and NetMHCpan, found that all three algorithms predict affinities several orders of magnitude away from measured values for most simulated peptides [ 23 ]. This shows that care must be taken when extrapolating the results of machine learning outside of the dataset used to train such models.…”
Section: Discussionmentioning
confidence: 74%
“…Off-rates predicted by online utilities were inconsistent not only with measured values but with each other, both in order of magnitude and in rank order of peptides, though they correctly predicted which peptides would bind poorly. Previous authors have made similar observations; a recent study evaluating performance of computational models in predicting CD8+ epitopes found that no existing algorithm performs ‘substantially’ better than random [ 22 ], and a study introducing MHCflurry, an MHC-I binding affinity prediction package that the authors present as an improvement over NetMHC and NetMHCpan, found that all three algorithms predict affinities several orders of magnitude away from measured values for most simulated peptides [ 23 ]. This shows that care must be taken when extrapolating the results of machine learning outside of the dataset used to train such models.…”
Section: Discussionmentioning
confidence: 74%
“…We previously reported that the existing immunogenicity algorithms showed suboptimal performance in predicting epitopes from both cancer and an emerging viral pathogen 7 . We then attributed the poor performance to divergent discriminative features between cancer neoepitopes and pathogenic epitopes in directionality or magnitudes 7,23 .…”
Section: Out-of-distribution Uncertainty and Hla Bias Results In Poor...mentioning
confidence: 99%
“…While in silico models that predict antigen presentation can be highly accurate (such as netMHCpan), state-of-the-art models predicting the subset of HLA ligands that then invoke T cell responses possess limited accuracy[36]. We recently developed TRAP, a Convolutional Neural Network (CNN) model that offers improved predictions of T cell recognition potential of HLA-I presented 9- and 10-mer peptides.…”
Section: Resultsmentioning
confidence: 99%
“…In that light, in silico studies e.g., the work by Nersisyan et al [29] compared all theoretical HLA ligands across specific VOC and concluded that T cell responses to Omicron were likely to be maintained effectively. However, not all HLA ligands can invoke T cell responses [35,36]. Furthermore, studies such as those of Naranbhai et al [17] and Reynolds et al [18] observed considerable numbers of patients with impaired T cell responses to Omicron infection [52].…”
Section: Discussionmentioning
confidence: 99%